Evaluación de la calidad educativa a partir del modelo EFQM para mejorar el sistema educativo - Bernardo Ortiz, Alexandra (2010)
This research artide focuses on the educational quality evaluation, which is under responsibility of the management body of an educational institution. The importance using proper evaluation tools - like the European Foundation for Quality Management (EFQM) model - should be taken into account, specially to achieve excellence based on the outcome of saidevaluation process.